Hygroscopic behavior of freeze-dried papaya pulp powder with maltodextrin - doi: 10.4025/actascitechnol.v36i1.17499 - Canuto, Holivania Maria Pereira; Afonso, Marcos Rodrigues Amorim; Costa, José Maria Correia da (Acta Scientiarum. Technology, 2013)
The sorption isotherms describe the relationship between water activity and equilibrium moisture content of foods at a certain temperature. This work was carried out to study the hygroscopicity of freeze-dried papaya pulp powder with maltodextrin at different concentrations using sorption isotherms constructed at 25Â° C. Three formulations of freeze-dried powders were prepared, papaya pulp powder, papaya pulp powder with maltodextrin 5% (w w-1) and papaya pulp powder with maltodextrin 15% (w w-1). In order to adjust the adsorption isotherms data, mathematical models of GAB, BET, Henderson and Oswin were used. The GAB model showed the best fit for all samples. The addition of maltodextrin increased the amount of water in the monolayer and reduced the hygroscopicity of the powders Â Â